Key components and strategies utilized by nurses for de-escalation of aggression in psychiatric in-patients: a systematic review protocol. (December 2016) - Shah, Lubna; Annamalai, Jancirani; Aye, Swe Nwe; Xie, Huiting; Pavadai, Singaravelan s/o; Ng, Warric; Suppiah, Kuganesh s/o; Shah, Abu; Manickam, Maragatham
Abstract : Review question/objective: This systematic review aims to identify the effective de-escalation strategies that nurses utilize to prevent aggressive behaviors. Specifically, this review has the following objectives: To explore effective strategies used by nurses to de-escalate aggression in patients in the psychiatric setting. To identify the key components of effective strategies in the de-escalation of aggression in patients by nurses in the psychiatric setting.